Identifikasi Spesies Mangrove dengan Menggunakan Sistem Pesawat Udara Kecil Tanpa Awak di Kawasan Ekosistem Mangrove Sedari, Kabupaten Karawang, Jawa Barat - Sewiko, Roni; Sagala, Herlina Adelina Meria Uli; Yulandhita, Yulandhita; Pattirane, Chrisoetanto P. (Nekton, 2022)
Remote sensing is one of the effective methods of monitoring mangrove ecosystems. One of the challenges in implementing this method is image resolution. Access to large-resolution imagery as a basic material for spatial analysis is not cheap. Unmanned small aircraft systems (SPUKTA) or drones are able to answer these challenges. Orthophotos obtained from the acquisition of drones are capable of producing large-resolution imagery. This method is then implemented in conservation areas, to facilitate the process of identifying mangrove species in the area. The drone was flown at an altitude of 150 m with a pavement value of 85% for 4 flying missions. The result of processing 1614 aerial photos into orthophotos produced images with a GSD resolution of 4.75 cm/pix. These images are then analyzed with on-screen digitization techniques and visual interpretation. From the total area of the study area of 46.48 ha obtained the digitization results of Rhizophora sp. with a total area of 24.68 ha, Avicennia sp. 7.64 ha, dead mangroves 0.19 ha, and non-vegetation 13.97 ha.